Legal Protection of BPJS Participants in Ngudi Waluyo Wlingi Hospital-Blitar District - Atiana, Sofyetin (Universitas PGRI Madiun, 2023)
This study aims to explain the legal protection of patients participating in BPJS Health in health services at Ngudi Waluyo Wlingi Hospital and the role of the government and the accountability of the hospital in fulfilling the rights of patients registered as BPJS Health participants. The empirical juridical research method is also called research examining law as a pattern of behavior shown in the application of legal regulations. The empirical juridical approach is carried out by collecting primary data information obtained directly in the field which is aimed at applying the law relating to the use of the family witness. Whereas in legally protecting BPJS Kesehatan participant patients in obtaining health services, there are two types of legal protection for BPJS participants in health services, namely preventive and repressive legal protection. There are two roles of the government and the responsibility of the hospital in fulfilling the rights of patients who are registered as BPJS Health participants. The first is to provide convenience for BPJS Kesehatan patients with the collaboration of BPJS Kesehatan and the â€œNgudi Waluyoâ€ Wlingi Hospital in educating patients/customers of BPJS Kesehatan participants by improving the quality of health services in hospitals. Second, pay attention to facilities and infrastructure for patient rights and follow up quickly on complaints/complaints from patients/customers participating in BPJS Kesehatan that there is no distinction between BPJS Kesehatan patients and/or incapacitated patients or general patients